2016
DOI: 10.3109/14397595.2016.1153449
|View full text |Cite
|
Sign up to set email alerts
|

Association of the multi-biomarker disease activity score with joint destruction in patients with rheumatoid arthritis receiving tumor necrosis factor-alpha inhibitor treatment in clinical practice

Abstract: (2016) Association of the multi-biomarker disease activity score with joint destruction in patients with rheumatoid arthritis receiving tumor necrosis factoralpha inhibitor treatment in clinical practice, Modern Rheumatology, 26:6, 850-856, DOI: 10.3109/14397595.2016

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The MBDA more effectively discriminated radiographic progressors from non‐progressors than the 44‐joint DAS (AUROC 0.767 versus 0.521) as well as CRP and ESR . Additionally, among those in low or moderate/high disease activity as determined by the DAS28, MBDA scores further discriminated risk of RP . In contrast, 2 studies demonstrated less capability of the MBDA score to predict RP .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The MBDA more effectively discriminated radiographic progressors from non‐progressors than the 44‐joint DAS (AUROC 0.767 versus 0.521) as well as CRP and ESR . Additionally, among those in low or moderate/high disease activity as determined by the DAS28, MBDA scores further discriminated risk of RP . In contrast, 2 studies demonstrated less capability of the MBDA score to predict RP .…”
Section: Resultsmentioning
confidence: 94%
“…Our search strategy identified an initial 718 studies, with 470 remaining after excluding duplicates (Figure ). Full‐text review of 121 studies was completed with exclusion of those reported only in abstract form (n = 98) or without original data (n = 1), resulting in 22 articles included in the systematic review . Eight studies showed correlations with RA disease activity measures and were included in the meta‐analyses .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, rate of radiographic progression over one year was greatest among patients with baseline MBDA scores in the high category (>44) and lowest among patients with baseline MBDA scores in the low category (<30) [9][10][11][12][13][14] . Patients with moderate MBDA scores (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) tended to have progression rates almost as low as those with low MBDA scores. Cross-classification analyses showed that the MBDA score predicted risk for radiographic progression even when it was discordant with DAS28-CRP or CRP, such as when the MBDA score was high and conventional measures indicated low disease activity 14 .…”
Section: Introductionmentioning
confidence: 99%
“…We would encourage readers to make the distinction between the scientific validity of a diagnostic test and its clinical utility. There is already a sizable evidence base supporting the development and validation of the MBDA test in diverse RA patient cohorts (9)(10)(11)(12)(13)(18)(19)(20)(23)(24)(25). A prospective clinical trial is underway to rigorously evaluate its clinical utility and its potential role in RA patient management (26).…”
Section: To the Editormentioning
confidence: 99%